2020
DOI: 10.21037/gs.2020.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Comparing LigasureTM Exact dissector with other energy devices in total thyroidectomy: a pilot study

Abstract: Background: Hemostasis is fundamental in thyroid surgery. The aim of this randomized active comparator-controlled study was to compare the effectiveness of Ligasure TM Exact to previously existing sealing devices in patients undergoing thyroidectomy.Methods: A total of 180 patients were randomly allocated into 4 groups according to the hemostatic device used: Focus Harmonic Scalpel ® (FHS), Ligasure TM Small Jaw (LSJ), Thunderbeat ® (TB), and Ligasure TM Exact (LE). We recorded epidemiologic and biochemical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…Ultimately, as regards the economic aspect, the gain in time leads to a decrease in the overall costs, which justifies the cost of the devices. Shorter operative times in thyroidectomies performed with TB compared with those with HF in our experience and in those of Back et al and Papavramidis et al [ 32 , 34 , 35 ], in our opinion, are due to a greater speed of TB in coagulation and cutting of tissues, probably resulting from the simultaneous use of two forms of energy.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Ultimately, as regards the economic aspect, the gain in time leads to a decrease in the overall costs, which justifies the cost of the devices. Shorter operative times in thyroidectomies performed with TB compared with those with HF in our experience and in those of Back et al and Papavramidis et al [ 32 , 34 , 35 ], in our opinion, are due to a greater speed of TB in coagulation and cutting of tissues, probably resulting from the simultaneous use of two forms of energy.…”
Section: Discussionsupporting
confidence: 55%
“…As regards the other four clinical studies in which TB was considered, in all of these, no statistically significant difference was found in terms of complications between HF and TB [ 33 , 34 , 35 , 36 ]. However, in this regard, it is important to underline that Back et al [ 34 ] reported a higher rate of transient recurrent laryngeal nerve injury in patients operated on with TB although the difference was not statistically significant (probably due to the limited size of their sample).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The identification and location of PGs is a wellknown challenge of thyroid or parathyroid surgery (14). Accidental injury or resection may lead to hypoparathyroidism, which means temporary or permanent hypocalcemia and other accompanying symptoms (15).…”
Section: Wwwbiosciencetrendscommentioning
confidence: 99%